Advanced Oracle PL/SQL Developer's Guide - Second Edition. - Gupta, Saurabh K. (Packt Publishing, Limited, 2016)
The OCP certification is the second milestone for the experienced associate level Oracle professionals which enhances one's credibility in work environment, and catalyzes your employment opportunities. The Packt's book Oracle Advanced PL/SQL Developer Professional Guide helps you to master the advanced PL/SQL concepts in Oracle 11g. The book aims to be a sure selection for the experienced Oracle professionals aspiring for Professional level by writing Oracle certification exam "1Z0-146: Oracle Database 11g: Advanced PL/SQL." The topics covered in the book are in line with the Oracle University prescription for 1Z0-146 certification, which justify the version updates to be advanced and not complex. The book has been reviewed by Oracle ACEs Kamran Agayev, Ronald Rood, Mohan Dutta, and Marcel Hoefs. The book covers the advanced features of PL/SQL which are required to design and optimize the PL/SQL code in database applications. The features like collections, external procedures, server side result caching, enforce row level security using VPD, handling large objects and SecureFiles build up a concrete platform for a PL/SQL professional. Apart from the programming, the book makes instrumental recommendations on the usage of development tool SQL Developer, employing best practices in database environments and safeguarding the vulnerable areas in PL/SQL code to avoid code injection.